KONTRIBUSI KEPEMIMPINAN KEPALA SEKOLAH DAN IMPLEMENTASI PERENCANAAN STRATEGIS TERHADAP MUTU HASIL BELAJAR: STUDI KASUS DI SEKOLAH SE-KECAMATAN CAKRANEGARA - Hapipi, Hapipi; Azizah, Yupiatul; Mustari, Mohammad (Berajah Journal, 2024)
This research aims to analyze the contribution of school principal leadership and implementation of strategic planning to improving the quality of learning outcomes in Cakranegara District schools. The method used is a qualitative approach with data collection techniques in the form of in-depth interviews, observation and documentation studies. Research participants consisted of school principals, teachers and staff involved in the learning process. Data were analyzed using thematic analysis to identify main themes related to leadership, strategic planning, and the quality of learning outcomes. The research results show that effective principal leadership, characterized by a clear vision, good management of resources, and the creation of a collaborative atmosphere, has a positive impact on the quality of teaching and student motivation. In addition, the implementation of thorough strategic planning increases the efficiency of resource management, thereby contributing to improving the quality of education. However, budget constraints and external support remain major challenges. This research concludes that synergy between school principals, teachers, parents and government is very important to achieve better quality education on a sustainable basis.